PENGARUH KOMUNIKASI NCTZEN INDONESIA TERHADAP PERILAKU MEMILIH NCT DREAM - Sari, Indah Purnama; Irawatie, Aniek; Kusumastuti, Retno Dyah (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2020)
Social media is a social change tool using the internet where social media used by everyone as their communication process that reaches all levels of society to form a group to talk about something that is in common with the group. NCTzen Indonesia is a fan group from the Kpop idol group, NCT Dream that formed from the social media Twitter, nctconfess. The nctconfess followers are considered to be able to influence the activities and behavior of other followers. This research aims to determine the effect of NCTzen Indonesia's communication through Twitter on the voting behaviour of fellow followers using the S-O-R theory as its foundation. This research uses the quantitative approach with a survey method in the form of questionnaires spread through menfess to 100 respondents in the category of followers of Nctconfess who vote in NCT Dream during the promotion period. The results based on the correlation test show that there is a strong relationship between NCTzen Indonesia's communication and voting behaviour. Referring to the test results of the coefficient of determination, they show that the magnitude of the effect generated by the Communication of NCTzen Indonesia (X) on the Voting Behavior (Y) is 39.81% and the remaining 60.19% is influenced by other factors outside this research.